Valdensek: az elmúlt századok egyedülálló életvitele - BOGNÁRNÉ KOCSIS, Judit (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Waldensians: The Unique Way of Life of the Past Centuries The Waldensians are fundamentally Protestants living in the valleys of the Alps. This group of people could be written about from numerous perspectives, examining various historical periods. The present study undertakes to focus on the main characteristics of the Italian Waldensians during the period from the medieval world to the early modern and modern ages. Although the examined period covers a quite broad span of time, I dared to highlight it; thus, beyond introducing the Waldensian culture, I find their attitude towards life particularly noteworthy. Although this presentation is not deep enough, it can provide sufficient information for those interested in the topic to continue reading about it. Within the marked theme, I would like to discuss the Waldensians’ physical appearance, their dress, their mental, spiritual, and physical activity, their attitude towards learning, problem solving, and their social competencies.